Dyssynchrony significantly increases myocardial stiffness at mitral valve closure. (4th February 2022) - Wouters, L; Duchenne, J; Bezy, S; Papangelopoulou, K; Puvrez, A; Klop, B; Voros, G; D"hooge, J; Voigt, JU
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWO: Fonds Wetenschappelijk Onderzoek (fund for Scientific Research Flanders) Background: Recently, shear wave elastography (SWE) has emerged as a promising, non-invasive technique to determine myocardial tissue stiffness. SWE is based on the detection of shear waves, for example induced by mitral valve closure (MVC), that propagate through the myocardium. The propagation speed of these shear waves is directly dependent on myocardial stiffness. However, the effect of a dyssynchronous contraction pattern – as it occurs in left bundle branch block (LBBB) – on shear wave speed is currently unknown. Purpose: To investigate the effect of the dyssynchronous contraction pattern caused by LBBB on shear wave speed. Methods: We included 25 non-ischemic heart failure patients with LBBB (age: 68 ± 15y; 52% males), all implanted with a CRT device. Dyssynchrony was reintroduced by turning biventricular (BiV) pacing off to allow native ventricular conduction. Echocardiographic images were taken during BiV pacing on and BiV pacing off, both with a conventional ultrasound machine and an experimental high frame rate ultrasound scanner (frame rate: 932 ± 32 fps). For SWE, left ventricular parasternal long-axis views were acquired. Shear waves were visualized in M-modes of the septum, colour coded for tissue acceleration. The slope of the shear waves in the M-mode represents their propagation speed. Speckle tracking of the four-chamber apical view was used to asses longitudinal strain of the mid-septal segment. To further investigate how dyssynchrony affects shear wave speed, the following time points were measured: onset of QRS, MVC and onset of septal contraction. Results: Acutely switching BiV pacing on and off did not significantly affect left ventricular ejection fraction, nor end-diastolic or end-systolic volumes (all p > 0.05). Shear wave speed was significantly higher during BiV pacing off compared to BiV pacing on (5.6 ± 1.2 m/s vs 4.9 ± 1.3 m/s; p = 0.003; figure A). Furthermore, the onset of septal contraction was significantly earlier during BiV off (11 ± 15 ms vs 105 ± 57 ms; p < 0.0001). As a result, during BiV pacing off, the septal wall was further into the contraction phase at the time of MVC, leading to an increased myocardial stiffness, and thus increased shear wave speed (figure B). Our interpretation that increased shear wave speed could be attributed to an earlier onset of contraction of the septum was further strengthened by a strong correlation between the change in shear wave speed and the change in septal longitudinal strain at MVC when BiV pacing is turned off (r = 0.83; p < 0.001; figure C). Conclusion: A dyssynchronous contraction caused by LBBB significantly increases shear wave propagation speed at MVC. This could be attributed to the early-systolic contraction of the septum during dyssynchrony. These results indicate that changes in contraction pattern caused by LBBB significantly influence myocardial stiffness at MVC.